Off Scaffolding and into the Deep End - Marsellas, Nick (Radical Teacher, 2019)
The practice of multicultural scaffolding, offering more information about an author’s marginalized identity, is frequently offered as the solution to challenging social justice discussions in the classroom. However, this type of scaffolding presupposes that intricate knowledge of another person's subjectivity is required for ethical classroom behavior. I argue, instead, that students are able to handle difficult topics with care if we train them to better work with the unintelligibility of others’ experiences. In an effort to reorient my classroom towards this engagement with unintelligibility, I have developed a framework called deep-end teaching, which encourages students to engage sensitive topics with a delicate balance of confidence and humility.